Penggunaan Media Pembelajaran Video Tutorial dalam Upaya Meningkatkan Kemandirian Belajar Peserta Didik - Hani Kustyanti Kusnadi; Asep Hidayat; Popon Mariam (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2018)
This research is motivated by the lack of learning independence of learners. Learners who have learning independence tend to learn better, be able to take decisions, think ahead, have a sense of responsibility towards learning, can organize learning effectively, save time learn efficiently and not depend on others emotionally. The facts in the field researchers found the problem is the lack of learning independence on the learning spreadsheet / processor numbers, one of the factors causing the lack of availability of learning media in accordance with the independence of learning.The purpose of this study is to test the video tutorial media in an effort to improve the independence of learning. Based on the results of data processing, it can be concluded that the use of tutorial video learning media more effectively used in learning spreadshee/processor numbers in improving the independence of learners learn than digital module spreadsheet